Development of Professional Competencies of The Future Costume Designer in the Design System - Faizulina, Elvira; Yessengaliyeva, Aliya; Jumagaliyeva, Venera (Harmonia: Journal of Arts Research and Education, 2024)
High requirements for specialists, specifically in the field of Design, who can quickly respond to modern socio-economic conditions and work effectively in a market economy necessitate a substantial upgrade of the professional education system for training costume designers. This study aimed to substantiate and implement the methodology for developing professional competencies of future costume designers in higher education institutions in Kazakhstan. The methodological approach of this experimental study was based on the development of a methodology for developing the professional competencies of the future costume designer and readiness components: motivational, cognitive-activity, creative, and reflective. The content of the basic terms “professional competence” and “designer’s professional competence” was determined; their signs and features were covered, and and a methodology for developing professional competencies of the future costume designer in the design system was developed and implemented. In the conducted experimental study at the ascertaining stage of the experiment at Makhambet Utemisov West Kazakhstan University, methodological tools were developed to increase the readiness of the future costume designer to develop professional competencies in the design system. After conducting an experimental study, promising areas for improving the methodology for the readiness of a future costume designer to develop professional competencies in the design system in higher educational institutions of Kazakhstan were formed. The practical value of the study lies in training a specialist who can implement scientific ideas and developments in the field of fashion design in Kazakhstan.